2012
DOI: 10.1037/a0024871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of message, source, and context on evaluations of employee voice behavior.

Abstract: The article contained a production-related error. In Table 5, the four values in the rows for Study 1 Prosocial motives and Study 1 Constructive voice should have been shifted one column to the right, to the Direct and Total Performance evaluations columns. All versions of this article have been corrected.] Although employee voice behavior is expected to have important organizational benefits, research indicates that employees voicing their recommendations for organizational change may be evaluated either posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
297
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(323 citation statements)
references
References 69 publications
(102 reference statements)
15
297
1
1
Order By: Relevance
“…In existing studies based on the social exchange theory [9], a typical viewpoint holds that because voice behavior can improve the team or organizational performance, supervisors should give a positive performance appraisal (i.e., high ratings) to employees who are willing to share their knowledge, ideas, and opinions for managerial problem solving. This viewpoint is supported by empirical studies which found that voice behavior is positively associated with the evaluation of employee performance [3,8,10,11]. In the existing literature, the voice is viewed as an aspect of citizenship behavior involving innovative suggestions that contribute toward changing existing practices and leading to improvements [12].…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…In existing studies based on the social exchange theory [9], a typical viewpoint holds that because voice behavior can improve the team or organizational performance, supervisors should give a positive performance appraisal (i.e., high ratings) to employees who are willing to share their knowledge, ideas, and opinions for managerial problem solving. This viewpoint is supported by empirical studies which found that voice behavior is positively associated with the evaluation of employee performance [3,8,10,11]. In the existing literature, the voice is viewed as an aspect of citizenship behavior involving innovative suggestions that contribute toward changing existing practices and leading to improvements [12].…”
Section: Introductionmentioning
confidence: 49%
“…Not only the identification of specific motives, but also the types of attributed motives influence supervisors' evaluations of subordinates [11]. Employees with a prosocial motive are perceived as having a strong desire to help coworkers, a concern for the wellbeing of others, and a desire to build positive relationships with colleagues, creating a positive organization climate and facilitating interpersonal harmony in the organization.…”
Section: Attribution Of the Motives And Performance Appraisal Of Emplmentioning
confidence: 99%
See 1 more Smart Citation
“…This research stream has focused on two forms of managerial reactions. First, earlier work on voice examined reactions in terms of employee outcomes including managers' evaluation of employee performance, level of competence, expertise as well as career outcomes (e.g., Seibert et al, 2001;Whiting, Maynes, Podsakoff, & Podsakoff, 2012). Second, more recent work focused on examining how managers react to the voiced idea by looking at voice endorsement (e.g., Burris, 2012;Fast et al, 2014;Sijbom et al, 2015aSijbom et al, , 2015b.…”
Section: Managers' Reactions To Voicementioning
confidence: 99%
“…By contrast, employees who overestimate their voice volume receive worse performance evaluations. Whiting, Maynes, Podsakoff, and Podsakoff (2012), seeking to make sense of some of the mixed findings on how voice influences employee outcomes, drew from persuasion research to develop a more comprehensive model. They outlined the importance of examining how attributes of the voice source (i.e., the employee), the receiver (i.e., the manager), the message, and the context may affect performance evaluations of voicing employees.…”
Section: Employee Outcomesmentioning
confidence: 99%